Phylogeny determines the role of helminth parasites in intertidal food webs. (25th June 2013) - Poulin, Robert; Krasnov, Boris R.; Pilosof, Shai; Thieltges, David W.
Summary: Parasites affect interactions among species in food webs and should be considered in any analysis of the structure, dynamics or resilience of trophic networks. However, the roles of individual parasite species, such as their importance as connectors within the network, and what factors determine these roles, are yet to be investigated. Here, we test the hypotheses that the species roles of trematode, cestode and nematode parasites in aquatic food webs are influenced by the type of definitive host they use, and also determined by their phylogenetic affiliations. We quantified the network role of 189 helminth species from six highly resolved intertidal food webs. We focused on four measures of centrality (node degree, closeness centrality, betweenness centrality and eigenvalue centrality), which characterize each parasite's position within the web, and on relative connectedness of a parasite species to taxa in its own module vs. other modules of the web (within‐module degree and participation coefficient). All six food webs displayed a significant modular structure, that is, they consisted of subsets of species interacting mostly with each other and less with species from other subsets. We demonstrated that the parasites themselves are not generating this modularity, though they contribute to intermodule connectivity. Mixed‐effects models revealed only a modest influence of the type of definitive host used (bird or fish) and of the web of origin on the different measures of parasite species roles. In contrast, the taxonomic affiliations of the parasites, included in the models as nested random factors, accounted for 37–93% of the total variance, depending on the measure of species role. Our findings indicate that parasites are important intermodule connectors and thus contribute to web cohesion. We also uncover a very strong phylogenetic signal in parasite species roles, suggesting that the role of any parasite species in a food web, including new invasive species, is to some extent predictable based solely on its taxonomic affiliations. Abstract : This study uncovers a very strong phylogenetic signal in parasite species roles within food webs, suggesting that the role of any parasite species in a web, including new invasive species, is to some extent predictable based solely on its taxonomic affiliations.